Development of Module With Concept Maps and Picture on The Diversity of Living Things Materials for Students Class VII Junior High School - Selly Epriani Renat; Ernie Novriyanti; Armen Armen (Bioeducation Journal, 2017)
The purpose of this study produce teaching materials in the form of modules that is equipped with concept maps and images for the seventh grade students of junior high school, valid and practical. This study uses three steps of the model 4-D namely, define, design, and development. Subject 4 validators, 2 teachers, and 20 students at 26 public Junior High School in Padang. The data in this study are primary data collected from the questionnaire validity and practicalities. Results of product testing are developed, acquired valid and very practical criteria of the results by the lecturers, teachers, and students.